Identifying Limitations Children's Play & Games - Marwany (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
One of the important activities that support the growth and development of early childhood is playing and games. This study aims to explain and describe the concept of playing and children's games. The research method used is descriptive qualitative with data collection techniques through reading and recording reference documents that discuss the concept of playing and children's games. The results of the study are that playing by children is oriented towards moving activities; activities are carried out with fun; and have an impact on children's cognitive abilities. While games are a system that regulates play activities based on names, rules, tools and media, rewards and punishments, and ethics. Keywords: playing, games, and children.